Lembaga Rechtsverwerking Dalam Sistem Pendaftaran Tanah Di Indonesia - Arief Rahman Hakim (Jatiswara, 2012)
In Indonesia, land registration is promulgated in articles 19 of UUPA. To follow up such article, then PP No 10 of 1961 is established. Both regulations require negative system within land registration. This becomes one of the shortcomings of PP No 10 of 1961 which is then completed by PP No 24 of 1997. PP No 24 of 1997 itself adheres to negative system with positive system tendency. Negative system in the land registration means that information or official statements described within land certificate (land book) is absolutely could be changed. Hence, everyone deserves or has a chance to file a lawsuit to the court as long as he/she is able to prove his/her legal right of land. Such a lawsuit can only be submitted within period of 5 years after the certificate published. As for positive system tendency indicate the active role of relevant official in the application of land registration. Such official has to examine the land record carefully. Hence, it is land registration requires long duration to publish (30 days for systematic way and 60 days for sporadic way) in order to give everyone a chance to submit a protest or objection.This policy is established to prevent error or mistake as well as to gain the conformity between land certificate (land book) and the physics of land. Furthermore, it is for the holder of certificate (either private person or legal entity) couldn’t be charged after 5 years of legally possessing such certificate as long as he/she obtain it on the basis of good faith as well as real occupation principles (article 32 (2) PP No 24 of 1997). It indicates that such article adopts the concept of “Rechtsverwerking” (Waiver of Right) established in Adat law as one of the causes of losing land’s right; it is called “rechtsverwerking” if someone or the holder of land right do not within long term exploit the land and it is occupied by other party through transfer of right which based on good faith.